Rhizobia inhabiting Clitoria ternatea L. in Anuradhapura District, Sri Lanka: An assessment of stress tolerance and genetic diversity - Tennakoon, P.T.M.K.C.; Rajapakse, S. (University of Jaffna, 2021)
Legume-Rhizobial symbiosis plays a greater agronomical and ecological significance as it provides fixed nitrogen through Biological Nitrogen Fixation. Clitoria ternatea is a leguminous plant that hosts a wide range of rhizobial strains. Even though it is a widely distributed plant, comprehensive information and studies conducted on the rhizobial - C. ternatea symbiosis is lacking in Sri Lanka. This study aimed to identify different stress-tolerant rhizobial strains inhabiting root nodules of C. ternatea growing in seven selected locations of Anuradhapura district of Sri Lanka. Twenty-eight pure rhizobial colonies were isolated and they were separately grown in ½ Lupin broths and were subjected to four different physiological conditions, pH, temperature, salinity, and drought. Most of the isolates were well-grown within the pH range of 5.0-8.0, the temperature range of 30-35 °C and at 0.2% Polyethylene glycol-8000 (PEG) concentration. There was no observable pattern in the growth of rhizobial strains in different physiological conditions. The twelve rhizobial strains which showed high tolerance to extreme physiological conditions were subjected to a combination of physiological stress conditions of pH 8.0, temperature 36 °C, 3.0 % NaCl and 0.4 % PEG. The maximum growth in combination physiological study was observed in a strain collected at the Palugaswewa site. According to the dendrogram prepared by the Enterobacterial Repetitive Intergenic Consensus (ERIC) profile, twelve strains are genetically diverse, as they belonged to11 clusters at 69.89 % of similarity level. These stress-tolerant rhizobial strains could be used for further studies on cross-inoculation of crop legumes as an alternative to the nitrogenous fertilizers.
Keywords: C.ternatea; ERIC; Genetic diversity; Rhizobium